Comparison of calcium absorptive and secretory capacities of segments of intact or functionally resected intestine during normo-, hypo-, and hyper-calcemia - N. Krishnamra (2018)
Absorptive and secretory capacities of six in situ intestinal loops of equal length were compared under the same calcium load and calcemic condition. The highest rate of calcium absorption was found in duodenum, colon, and proximal jejunum when loops were filled with 0.3 mM calcium, and in duodenum and proximal jejunum when filled with 10 mM luminal calcium. Secretory rates were in the following order: duodenum, jejunum, proximal jejunum, cecum, ileum, and proximal colon. Absorption of 0.3 mM calcium was decreased in all but the cecum and colon during hypercalcemia, and in duodenum, proximal jejunum, and colon during thyroparathyroidectomy-induced hypocalcemia. In contrast, calcium secretion was directly related to plasma calcium concentration and the length of the intestine. Functional resection of any part met with a compensatory increase in calcium absorption by the remaining segments, with the exception of the resection of the distal ileum with the large bowel. In conclusion, proximal small intestine exhibited the highest rate of absorption and secretion, but functional resection of this or any part did not affect the overall calcium absorption if luminal calcium was 10 mM. Moreover, enhanced secretion and reduced absorption during hypercalcemia were beneficial with respect to plasma calcium regulation.